A 0.4 V, 6.4 nW, −75 dBm Sensitivity Fully Differential Wake-Up Receiver for WSNs Applications - Liao, Xufeng; Xie, Suzhen; Xu, Jiaxi; Liu, Lianxi (IEEE transactions on circuits and systems. I, Regular papers, 2022)
This paper presents a fully differential wake-up receiver (WuRX) with ultra-low power and high sensitivity. Implementing the fully differential framework achieves differential signal processing without an off-chip balun, which achieves noise suppression and sensitivity improvement. The low voltage baseband signal processing (LVBSP) is proposed to cut down the power consumption, which is achieved by the low-voltage fast-response differential amplifier (LFDA) and the time-domain signal processing circuit. Moreover, the periodic offset cancellation technique (POCT) in the baseband circuit is proposed to alleviate the offset and low-frequency noise impacts. This WuRX is implemented in the TSMC 65-nm CMOS process occupying an active area of 0.18 mm 2 . When operating at 434 MHz, the proposed WuRX has a −75-dBm sensitivity at 250 bps while consuming 6.4 nW from 0.4 V supply voltage.